2015
DOI: 10.1038/nmeth.3490
|View full text |Cite
|
Sign up to set email alerts
|

Mutational interference mapping experiment (MIME) for studying RNA structure and function

Abstract: RNA regulates many biological processes; however, identifying functional RNA sequences and structures is complex and time-consuming. We introduce a method, mutational interference mapping experiment (MIME), to identify, at single-nucleotide resolution, the primary sequence and secondary structures of an RNA molecule that are crucial for its function. MIME is based on random mutagenesis of the RNA target followed by functional selection and next-generation sequencing. Our analytical approach allows the recovery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
88
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 62 publications
(92 citation statements)
references
References 35 publications
4
88
0
Order By: Relevance
“…Until recently SL3, which is present downstream of mSD, had been proposed to be the main HIV-1 packaging signal since it harbors a conserved region containing a GGAG tetraloop that has been shown to bind NC [43]. However, it has now been shown that SL1, in addition to containing the HIV-1 DIS, also harbors a single-stranded purine rich internal loop (ssPurine: GAGG) that acts as the main site for HIV-1 Gag binding during gRNA packaging [26,30,44,45]. This internal ssPurine loop as well as the DIS, however, are located upstream of the mSD and therefore are part of both the spliced and unspliced viral mRNA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Until recently SL3, which is present downstream of mSD, had been proposed to be the main HIV-1 packaging signal since it harbors a conserved region containing a GGAG tetraloop that has been shown to bind NC [43]. However, it has now been shown that SL1, in addition to containing the HIV-1 DIS, also harbors a single-stranded purine rich internal loop (ssPurine: GAGG) that acts as the main site for HIV-1 Gag binding during gRNA packaging [26,30,44,45]. This internal ssPurine loop as well as the DIS, however, are located upstream of the mSD and therefore are part of both the spliced and unspliced viral mRNA.…”
Section: Discussionmentioning
confidence: 99%
“…This internal ssPurine loop as well as the DIS, however, are located upstream of the mSD and therefore are part of both the spliced and unspliced viral mRNA. Thus, in the case of HIV-1, selection of the gRNA for packaging is likely to be dependent upon the higher order structure of the major packaging determinant of the gRNA which is disrupted upon splicing [26,30,44,45]. In the case of HIV-2, even though both the spliced and unspliced viral mRNAs harbor RNA packaging sequences, only the unspliced message is packaged into nascently formed virus particle since HIV-2 Gag preferentially package gRNA in cis [46–48].…”
Section: Discussionmentioning
confidence: 99%
“…1; Jaballah et al 2010;Aktar et al 2013). LRIs have been found to be conserved in several retroviruses, including HIV-1 and 2, simian immunodeficiency virus (SIV), feline immunodeficiency virus (FIV), and mouse mammary tumor virus (MMTV) (Paillart et al 2002(Paillart et al , 2004bAbbink and Berkhout 2003;Kenyon et al 2008Kenyon et al , 2011Aktar et al 2014;Siegfried et al 2014;Keane et al 2015;Smyth et al 2015;Tran et al 2015). Despite the fact that there are substantial sequence heterogeneities among human, simian, and feline lentiviruses, the preservation of such LRIs in these lentiviruses suggest they play important function(s) in the retroviral life cycle (Paillart et al 2002;Kenyon et al 2008Kenyon et al , 2011.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the packaging sequences are eliminated during splicing, thereby excluding the spliced RNAs from encapsidation into the nascent viral particles. However, in the case of HIV-1, the main determinant of Gag binding, stem-loop 1 (SL1) is located upstream of the major splice site (Abd El-Wahab et al 2014;Smyth et al 2015) and is thus present in both the spliced and unspliced viral mRNA, revealing a more complex mechanism of gRNA selection in which the gRNA structure plays a key role (Abd El-Wahab et al 2014;Smyth et al 2015). A similar situation also prevails in HIV-2 as both the spliced and unspliced viral mRNAs contain the packaging determinants, yet only the unspliced messages are encapsidated into the virus particle (for review, see Balvay et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…For example, the poly(A) stem loop of HIV-1 is involved in long-range interactions (LRIs) with sequences in the matrix (MA), forming a pseudoknot [71]. Similarly, the U5 stem loop sequences are involved in long-range interactions (LRI) with the stem loop containing the Gag AUG in many retroviruses, including HIV-1 and 2, SIV, FIV, MMTV, and MPMV [69,70,71,72,73,74,75,76,77,78,79], as well as other plus-strand RNA viruses with icosahedral capsids [80]. Mutations that destabilize these interactions affect several important steps in the retroviral replication cycle, including RNA packaging and dimerization [10,48,49,71,72,79,81,82].…”
Section: How Similar Is the Structural Organization Of Packaging Ementioning
confidence: 99%